Family Reunification of Foreign Minors in Navarre: An Analytical Proposal through Five Stages - Lasheras Ruiz, Rubén; Jabat Torres, Edurne; Andueza Imirizaldu, Izaskun (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
Family reunification, as a phenomenon linked to migrations, allows the reunion of people (previously grouped as a family) after living geographically and temporarily separated. The aim of this paper is to study in depth the effects of family reunification of minors of foreign origin in Navarra (Spain). Through qualitative techniques (biographical interviews and focus groups), impacts on both reunited and reuniting persons are identified. The results, presented through a five-stage analytical approach, highlight, first, need-driven departures punctuated by grief, guilt and misunderstanding. Subsequently, prolonged parental-filial separations occur, fracturing ties. The decision to reunite also collides with legal requirements, leading to de facto reunifications that generate lack of protection. Likewise, reunions are fraught with estrangement and clashes. Finally, during the process of fitting in, obstacles (work, education, etc.) to reintegration and social belonging are encountered. In short, these transnational families are strained by suffering and structural constraints.